Oxidation of paracetamol by N-chloro-p-toluene sulfonamide (Chloramine-T) in aqueous acid perchlorate medium: A kinetic and mechanistic pathway (Indian Journal of Chemistry (IJC), 2023)
Kinetics and mechanism of oxidation of paracetamol by N-chloro-p-toluene sulfonamide (chloramine-T) have been studied in acid medium. Accounting for all such observations, a plausible reaction mechanism has been suggested. The activation parameters such as energy and entropy of activation have been calculated to be (58.63 ± 0.91) kJ mol−1 and (−88.75 ± 4.54) J K−1 mol−1 respectively employing Eyring equation. The stoichiometry of the reaction has been observed to be two moles of the oxidant for a mole of the substrate. The rate of the reaction is retarded by toluene-p-sulfonamide as well as hydrogen ion concentration. The oxidation product of paracetamol has been spectrally confirmed to be quinine oxime. To further support our proposed mechanism, density functional theory (DFT) computations at M06-2X/6-31G(d,p) level of theory have been performed, showing that activation energy barriers predict the same reactivity trend as shown by the kinetic experiments.